DINAMIKA PEMBAURAN IDENTITAS TIONGHOA MUSLIM DI PALEMBANG - Rohim Pahrozi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
The aim of this research is to reveal the ethnic identity of Tionghoa Moslem in Palembang. An important theme related to Chinese ethnic in keeping their Chinese identity amid the plurality of Indonesian society and culture in everyday life in Palembang will be revealed. Is there a conflict in the majority Muslim community, where this group has dual identity, China and moslem. Social identity theory is chosen as a theoretical tool to understand the problem of this research. This research was conducted in Palembang by involving several samples of research subjects from moslem of Chinese Totok to moslem of Chinese descent. This research is a qualitative research by using symbolic interactionist approach. This approach focuses on the personal aspects of the subject of research aimed to identifying the emerging social dynamics associated with ethnic Chinese that living in Palembang in maintaining their social identity while interacting with other social identities. Determination of informants using the principle of snowball. Technique of collecting data through interview, observation and documentation, and analyzed by using descriptive qualitative.